2016
DOI: 10.1097/icb.0000000000000188
|View full text |Cite
|
Sign up to set email alerts
|

Development of Epstein–barr Virus Uveitis After Remission of Primary Vitreoretinal Lymphoma

Abstract: Purpose: To describe a case of Epstein-Barr virus (EBV) uveitis that occurred after the treatment and remission of primary vitreoretinal lymphoma (PVRL).Methods: Descriptive case report. Complete ophthalmologic evaluation, cytology, polymerase chain reaction, cytokine analysis of aqueous humor, and diagnostic vitrectomy were performed.Results: A 66-year-old Caucasian woman developed uveitis in the same eye 20 months after remission of PVRL. Empiric chemotherapy failed to treat the suspected PVRL recurrence, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…Conversely, Chahal et al. (2016) described a case of a patient suffering from AAU 20 months after PVRL remission that was treated with topical steroid treatment and highlighted the importance of considering EBV in cases of suspected recurrence of PVRL with ineffective chemotherapy treatment. Moreover, recent studies suggest that patients with uveitis and high intraocular levels of EBV DNA or anti‐EBV antibodies appear to be at increased risk for HIV infection, including several patients with PVRL (Cunningham & Zierhut 2020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, Chahal et al. (2016) described a case of a patient suffering from AAU 20 months after PVRL remission that was treated with topical steroid treatment and highlighted the importance of considering EBV in cases of suspected recurrence of PVRL with ineffective chemotherapy treatment. Moreover, recent studies suggest that patients with uveitis and high intraocular levels of EBV DNA or anti‐EBV antibodies appear to be at increased risk for HIV infection, including several patients with PVRL (Cunningham & Zierhut 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Acute anterior uveitis (AAU) has been reported in a case series of EBV infections. Unlike AAU caused by other herpes viruses, EBV usually is neither hypertensive nor granulomatous (Morishima et al 1996;Chahal et al 2016;Ban et al 2020). Cigni et al (2003), Grefer et al (1999) reported a case of a middle-aged women with anterior uveitis associated with tubulointerstitial nephritis (TINU) after EBV infection.…”
Section: Ebv and Anterior Segment Inflammationmentioning
confidence: 99%